Molecular cloning and differential expression patterns of sigma and omega glutathione S-transferases from Venerupis philippinarum to heavy metals and benzo[a]pyrene exposure - 张林宝 吴惠丰 刘小莉 陈磊磊 王清 赵建民 由丽萍 (Chinese journal of oceanology and limnology, 2012)
Glutathione S-transferases （GSTs） are a class of enzymes that facilitate the detoxification of xenobiotics, and also play important roles in antioxidant defense. We identified two glutathione S-transferase isoforms （VpGSTS, sigma GST; VpGSTO, omega GST） from Venerupis philippinarum by RACE approaches. The open reading frames of VpGSTS and VpGSTO were of 612 bp and 729 bp, encoding 203 and 242 amino acids with an estimated molecular mass of 22.88 and 27.94 kDa, respectively. The expression profiles of VpGSTS and VpGSTO responded to heavy metals and benzo[a]pyrene （B[a]P） exposure were investigated by quantitative real-time RT-PCR. The expression of VpGSTS and VpGSTO were both rapidly up-regulated, however, they showed differential expression patterns to different toxicants. Cd displayed stronger induction of VpGSTS expression with an approximately 12-fold increase than that of VpGSTO with a maximum 6.4-fold rise. Cu exposure resulted in similar expression patterns for both VpGSTS and VpGSTO. For B[a]P exposure, the maximum induction of VpGSTO was approximately two times higher than that of VpGSTS. Altogether, these findings implied the involvement of VpGSTS and VpGSTO in host antioxidant responses, and highlighted their potential as a biomarker to Cd and B[a]P exposure.